2013
DOI: 10.5858/arpa.2012-0485-oa
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lymph Nodes for Tumor Staging: Appraisal of 871 Nephrectomies With Examination of Hilar Fat

Abstract: Context.-Despite decades of research, the role of lymphadenectomy in the management of renal cell carcinoma (RCC) is still not clearly defined. Before the implementation of targeted therapies, lymph node metastases were considered to be a portent of markedly decreased survival, regardless of the tumor stage. However, the role of lymphadenectomy and the relative benefit of retroperitoneal lymph node dissection in the context of modern adjunctive therapies have not been conclusively addressed in the clinical lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…found metastases only in grossly identifiable lymph nodes, suggesting that random microscopic assessment of hilar fat for microscopic lymph nodes may be unnecessary. It is of note that a considerable number of non‐hilar lymph nodes were also found, with a lower rate of positivity (65% hilar; 16% non‐hilar), suggesting that some attention should be paid to possible lymph nodes in other areas of nephrectomy specimens. Previous staging systems have included additional categories for renal cancer depending on the size and number of involved lymph nodes; however, the current AJCC system, like the previous version, continues to include only pN1 for involvement of one or more regional lymph nodes .…”
Section: Lymph Nodesmentioning
confidence: 99%
“…found metastases only in grossly identifiable lymph nodes, suggesting that random microscopic assessment of hilar fat for microscopic lymph nodes may be unnecessary. It is of note that a considerable number of non‐hilar lymph nodes were also found, with a lower rate of positivity (65% hilar; 16% non‐hilar), suggesting that some attention should be paid to possible lymph nodes in other areas of nephrectomy specimens. Previous staging systems have included additional categories for renal cancer depending on the size and number of involved lymph nodes; however, the current AJCC system, like the previous version, continues to include only pN1 for involvement of one or more regional lymph nodes .…”
Section: Lymph Nodesmentioning
confidence: 99%
“…Mehta et al (27) examined the entire hilar tissue for histology and found that 80% of grossly visible lymph nodes were positive for tumor, whereas microscopic lymph nodes were all benign.…”
Section: Gross Examination For Lymph Nodesmentioning
confidence: 99%
“…This may in part be because of limited pathologic examination of adjacent renal hilar fatty tissue, as it has been reported to have a low yield for nodes, which are typically negative in adult malignancies. 11 Our results suggest that en bloc only resection of LNs should be avoided as the sole method of sampling with WT. We recommend that surgeons attempt to remove nodes with the tumor specimen, and also submit additional paraaortic, paracaval, and hilar nodes to pathology, as this method yields the most LNs for pathologic evaluation.…”
Section: Discussionmentioning
confidence: 70%